The Spelling Skills of French‐Speaking Dyslexic Children. (11th April 2013) - Plisson, Anne; Daigle, Daniel; Montésinos‐Gelet, Isabelle
Abstract : Learning to spell is very difficult for dyslexic children, a phenomenon explained by a deficit in processing phonological information. However, to spell correctly in an alphabetic language such as French, phonological knowledge is not enough. Indeed, the French written system requires the speller to acquire visuo‐orthographical and morphological knowledge as well. To date, the majority of studies aimed at describing dyslexic children's spelling abilities related to English and reading. The general goal of this study is to describe the spelling performance, from an explanatory perspective, of 26 French‐Canadian dyslexic children, aged 9 to 12 years. The specific goals are to describe the spelling performances of these pupils in the context of free production and to compare them with the performances of 26 normally achieving children matched on age (CA) and with those of 29 younger normally achieving children matched on reading age (RA). To do so, errors were classified according to phonological, visuo‐orthographical and morphological properties of French written words. The results indicate that the dyslexic group scored lower than the CA group but sometimes also lower than the RA group. The results are discussed according to the types of knowledge required to spell correctly in French. Copyright © 2013 John Wiley & Sons, Ltd.